2019
DOI: 10.1029/2018jd029688
|View full text |Cite
|
Sign up to set email alerts
|

VIIRS Deep Blue Aerosol Products Over Land: Extending the EOS Long‐Term Aerosol Data Records

Abstract: A primary goal of the Deep Blue (DB) project is to create consistent long‐term aerosol data records, suitable for climate studies, using multiple satellite instruments. In order to continue Earth Observing System (EOS)‐era aerosol products into the Joint Polar Satellite System era, we have successfully ported the DB algorithm to process data from the Visible Infrared Imaging Radiometer Suite (VIIRS). Although the basic structure of the VIIRS algorithm is similar to that for the Moderate Resolution Imaging Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(131 citation statements)
references
References 40 publications
3
117
0
Order By: Relevance
“…The VIIRS DB algorithm provides retrievals on every day except the thickest few when the AERONET daily mean AOD at 550 nm was above 5. Although VIIRS does have a broader swath than MODIS, the primary reason for this extra coverage is the additional relaxation of cloud masking tests in cases of heavy smoke, designed to retain such events (Hsu et al, ). However, for this case, the whole of September–October is masked out by the QA flag, which is intentional as these extreme conditions are expected to be inherently more uncertain and more likely to suffer from cloud contamination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The VIIRS DB algorithm provides retrievals on every day except the thickest few when the AERONET daily mean AOD at 550 nm was above 5. Although VIIRS does have a broader swath than MODIS, the primary reason for this extra coverage is the additional relaxation of cloud masking tests in cases of heavy smoke, designed to retain such events (Hsu et al, ). However, for this case, the whole of September–October is masked out by the QA flag, which is intentional as these extreme conditions are expected to be inherently more uncertain and more likely to suffer from cloud contamination.…”
Section: Resultsmentioning
confidence: 99%
“…2.2.2. MODIS/VIIRS DB The C6.1 MODIS DB retrieval algorithm (Hsu et al, 2019) is a refinement of the previous C6. Like DT, DB provides AOD at 550 nm with a nominal 10-km nadir pixel size.…”
Section: Modis Dtmentioning
confidence: 99%
See 1 more Smart Citation
“…In (c) and (e), Chou et al (2008) is not used in regressions due to the insignificant number of analyzed particles for HWR. In (e), values of the ratio of dust length to its height for climate models and retrieval algorithms are based on Mahowald et al (2014), Dubovik et al (2006), Hsu et al (2019), and Kalashnikova and Kahn (2006), respectively. MISR v23 is unity for diameter <0.16 μm and offset for clarity.…”
Section: Measurement Compilation Of Dust Shape Descriptorsmentioning
confidence: 99%
“…O'Neill et al (2000) showed that AOD derived from Sun photometer measurements at a variety of individual Aerosol Robotic Network (AERONET) sites spread around the world tends to have frequency distributions which statistically resemble a lognormal distribution to a much stronger degree than normal. All these previous studies were of data aggregated over time summarised at individual locations; around the same time, providing an early satellite example, Ignatov and Stowe (2000) found approximately log-normal AOD (and normal α) in aerosol retrievals over ocean scenes. This indicated that log-normal tendencies might be found in AOD data also aggregated spatially as opposed to just temporally.…”
mentioning
confidence: 98%